2014
DOI: 10.1037/a0035720
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from teacher depression and child-care quality to child behavioral problems.

Abstract: Results of this study suggest that teachers' depressive symptoms can be a contributor to global environmental child-care quality and to child externalizing and internalizing behavioral problems. Practical implications are that programs and policies must take into account effects of teacher depression on child-care quality and young children's school readiness regarding behavioral problems. Future research should further explore these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 52 publications
4
63
0
4
Order By: Relevance
“…As we expected, a higher psychological load was significantly associated with teachers' negative responsiveness-it was associated with an increase in the likelihood of punitive and minimizing reactions to children's negative emotions, although it explained only a small amount of the variance. Though this study is the first to examine teachers' responses to children's negative emotions as outcomes, our findings are similar to those of previous studies finding that early childhood teachers' depression (Jeon et al, 2014;Sandilos et al, 2015) and stress (Zinsser et al, 2013) predicted lower scores on observed classroom quality. It is possible that teachers with more psychological difficulties display negative emotions or moods with children because they lack the resources and time to manage their psychological issues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As we expected, a higher psychological load was significantly associated with teachers' negative responsiveness-it was associated with an increase in the likelihood of punitive and minimizing reactions to children's negative emotions, although it explained only a small amount of the variance. Though this study is the first to examine teachers' responses to children's negative emotions as outcomes, our findings are similar to those of previous studies finding that early childhood teachers' depression (Jeon et al, 2014;Sandilos et al, 2015) and stress (Zinsser et al, 2013) predicted lower scores on observed classroom quality. It is possible that teachers with more psychological difficulties display negative emotions or moods with children because they lack the resources and time to manage their psychological issues.…”
Section: Discussionsupporting
confidence: 90%
“…Studies support preschool teachers' psychological state as an important indicator of classroom quality and child outcomes (e.g., Hamre & Pianta, 2004;Jeon, Buettner, & Snyder, 2014;Whitaker, Dearth-Wesley, & Gooze, 2015), as excessive psychological burdens can hamper teachers' abilities to engage meaningfully with children and to maintain their professional commitment. For example, depression typically reduces an individual's interest, motivation, and vigor in everyday activities (American Psychiatric Association, 2013), which can be destructive to a teacher's ability to attend to children's emotions, provide supportive responses, and engage meaningfully in the teaching profession.…”
Section: Teachers' Social-emotional Capacitymentioning
confidence: 99%
“…This study provides foundational evidence for the high-risk nature of teaching as an occupation in relation with practitioners' emotional well-being. When these considerations are paired with strong evidence that teachers' psychological health is an important source of influence on a wide range of contributors to student development, such as classroom experience (Hamre & Pianta, 2004), behavior patterns (Jeon, Buettner, & Snyder, 2014), and cognitive/selfregulatory development (Ursache, Blair, & Raver, 2012), it becomes clear that mental health should be a higher priority within today's education system.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Jennings and Greenberg's (2009) prosocial classroom model highlights the importance of teachers' social and emotional competence and well-being in promoting healthy teacher-student relationships, effective classroom management, and effective social and emotional learning programs. Early childhood professionals' psychological well-being, such as depression, stress, burnout, and emotional competence (e.g., mindfulness, emotional regulation, coping), has been shown to relate to their practices and responsiveness in the ECE setting (Buettner, Jeon, Hur, & Garcia, 2016;Hamre & Pianta, 2004;Jennings, 2015), their relationships with children (Whitaker, Dearth-Wesley, & Gooze, 2015), as well as children's social-emotional development (Jeon, Buettner, & Snyder, 2014;Roberts, LoCasale-Crouch, Hamre, & DeCoster, 2016).…”
Section: Introductionmentioning
confidence: 99%